Transcendental Phenomenology and Transcendental Aesthetics in Edmund Husserl’s Philosophy: Originality and Primordiality in Life-world - Sánchez Soberano, Ramsés Leonardo (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
The purpose of this article is to explain the relationship between Life-world (Lebenswelt) and the concepts of Originality (Originalität) and Primordiality (Primordialität) founded in Edmund Husserl’s philosophy developed in the 20’s. In order to achieve this goal, we need to begin with a transcendental phenomenological analysis to then gain access to Ontology of the World in general. Therefore, we must explain how Transcendental Philosophy relates to Transcendental Aesthetics and how it phenomenologically labels all that is outside of theory and reflection (i.e., the Natural World) as a precondition to all theoretical classifications. This way the Life-world could explain the relationship between the Originality and Primordiality as proto-datum that is the base of all human acts genetically describable.
Keywords: originality; primordiality; life-world; transcendental aesthetics; transcendental phenomenology